Heterogeneous impacts of macroprudential policies: Financial advisors, regulatory caps, and mortgage risk - Martin Cesnak; Andrej Cupák; Pirmin Fessler; Ján Klacso (Oesterreichische Nationalbank (OeNB), 2025)
This paper examines the impact of borrower-based macroprudential policy tightening on mortgage lending in Slovakia, focusing in particular on the role of financial advisors in shaping loan characteristics. Using a comprehensive loan-level dataset from Slovak banks, we analyze the effects of key regulatory tools - Loan-to-Value (LTV), Debt-to-Income (DTI), and Debt Serviceto-Income (DSTI) limits - on mortgage risk profiles. Our contributions include: (1) showing that restrictive borrower-based measures (BBMs) reduce the riskiest loans but push lower-risk segments toward regulatory thresholds, thus increasing portfolio risk; (2) demonstrating that advisor-mediated loans tend to have higher amounts, LTVs, DTIs, and longer maturities, raising their riskiness; and (3) finding that strict enough DSTI limits not only reduce DSTI but may also indirectly effect other loan characteristics, such as DTI, LTV ratios, and loan volumes, suggesting broader policy impacts. Additionally, we identify significant front-loading behavior following policy tightening announcements, particularly for advisor-mediated loans. These findings highlight the importance of detailed micro-level data in capturing policy effects and informing more effective macroprudential regulation.
Keywords: G21; D18; D12; 330; debt behavior; financial advice; macroprudential policy; policy evaluation; heterogeneous effects; register microdata